AKUNTABILITAS PENGGUNAAN DANA DESA 2020 DI DESA BLEMBEM, KECAMATAN JAMBON, KABUPATEN PONOROGO - Subiyantoro Subiyantoro (Master of Public Administration, Universitas Slamet Riyadi, 2021)
Accountability in general can be defined as a demand for accountability forfulfilling responsibilities. Accountability really determines the success of policyimplementation, especially public policy by the government. The level of budgetabsorption and management of village funds which continues to experience positiveincreases from year to year, but in terms of the accountability report, it has notcarried out village financial administration properly. On the basis of theseproblems, this study aims to analyze and describe the accountability of village fundmanagement in Blembem Village, Jambon District, Ponorogo Regency in 2020. Theaccountability theory in this study uses Ellwood in Mardiasmo (2009: 21) that themanagement of village funds must be based on honesty and accountability law,accountability process, accountability program and accountability policy.This study uses a descriptive method with a qualitative approach. Researchinformants using purposive sampling technique. Data collection techniques usingin-depth interviews and documentation. The data analysis technique used isinteractive analysis consisting of data collection, data condensation, datapresentation and conclusion drawing.The results showed that the Blembem Village Government in managing villagefunds had shown accountability, both from the dimensions of honesty and legalaccountability, process accountability, program accountability and policyaccountability. From the accountability of honesty and law, it is evident that theyare willing to inform community members about the amount of village fundsreceived, do not abuse their positions, do not mark up budgets, and run accordingto Permendagri No. 113 of 2014 concerning Village Financial Management. Thedimension of process accountability shows that the procedures used in managingvillage funds are quite good in terms of the adequacy of accounting informationsystems, management information systems, and administrative procedures. In termsof program accountability, it shows that the programs that have been implemented,such as training programs for small industry businesses (sewing training, cakemaking training, etc.) can benefit the community and can improve the economy andcommunity welfare, even in terms of the capacity of village officials and training atMSMEs still needs optimization and assistance.Keywords: Honesty and Legal Accountability, Process Accountability, ProgramAccountability, Policy Accountability.